Hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin: kinetic studies - Diwakar, Makarand M.; Deshpande, R. M.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2005)
The exchange of the Rh/Triphenylphosphine trisulfonate sodium [TPPTS] complex on to an anion exchange resin results in a stable heterogenized catalyst for the hydroformylation of alkenes. The kinetics of hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin to Amberlite IRA-93 has been investigated for the first time. The rate of the reaction was found to be dependent on the partial pressure of hydrogen and 1-hexene concentrations with a first order. A maximum in the rate with increasing partial pressure of carbon monoxide was observed. A rate model has been proposed which predicts the observed rate data within reasonable error. The activation energy was found to be 84.37 kJ/mol. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogenized catalyst; Hydroformylation; ion-exchange resin; kinetics; Rhodium

Hydroformylation of olefins using dispersed molecular catalysts on solid supports - Pagar, N. S.; Deshpande, R. M.; Chaudhari, Raghunath V. (Catalysis Letters, 2006)
A new method for heterogenization of metal complex catalysts by precipitation of its water-soluble analogue as a Gr.2 metals (Ca, Sr or Ba) salt on porous supports has been proposed. This technique yields a highly dispersed catalyst having a significantly higher activity (TOF) for hydroformylation of olefins compared to other known heterogenized catalysts. The catalyst can be recycled with ease.
Keywords: carbon support; Heterogenization; Hydroformylation; Olefins; Rhodium

Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide

Highly regioselective isomerizing hydroformylation of long-chain internal olefins catalyzed by a rhodium bis(phosphite) complex - Pandey, Swechchha; Chikkali, Samir H. (ChemCatChem, 2015)
The single-step synthesis, coordination behavior, and application of a bis(phosphite) ligand in the isomerizing hydroformylation of internal olefins was investigated. Interestingly, high-pressure NMR spectroscopy investigations revealed unexpected inequivalency of the two phosphorus nuclei, which display bisequatorial coordination of the bis(phosphite) ligand in a trigonal bipyramidal rhodium complex. Upon employment in the isomerizing hydroformylation of the exceedingly challenging plant oil derived substrate methyl oleate, the bis(phosphite) rhodium complex revealed an unprecedented linear selectivity of 75%.
Keywords: alkenes; bis(phosphite)s; Hydroformylation; isomerization; Rhodium

Exploring activity differences between the hydroformylation catalysts: Insights from theory - Dangat, Yuvraj B.; Rizvi, Masood Ahmad; Pandey, Pippalad; Vanka, Kumar (Journal of Organometallic Chemistry, 2016)
Hydroformylation catalysis is the most important homogeneous catalysis process of the current day. The current computational investigation aims to understand the nature of the hydroformylation process when monodentate ligands are employed. The complete catalytic cycle for different monodentate ligands bound to the rhodium center has been studied with full quantum chemical calculations, with density functional theory (DFT). To the best of our knowledge, this is the first systematic investigation of the relative free energy surfaces for mono-coordinate monodentate and bi-coordinated monodentate ligands in hydroformylation catalysis. The results indicate that the barriers are lower for the mono-coordinate monodentate species in comparison to the bi-coordinate monodentate, for all the ligand cases studied, indicating higher activity for the mono-coordinate monodentate active species. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Density functional theory (DFT) calculations; Hydroformylation; Monodentate; Rhodium

Kinetics of hydroformylation of 1-decene using carbon-supported ossified HRh(CO)(TPPTS)(3) catalyst - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2019)
The kinetics of hydroformylation of 1-decene has been investigated using a carbon-supported ossified HRh(CO)(TPPTS)(3)/Ba catalyst in a temperature range of 343-363 K. The effect of concentration of 1-decene, catalyst loading, partial pressure of H-2 and CO, and stirring speed on the reaction rate has been investigated. A first-order dependence was observed for catalyst concentration and hydrogen partial pressure. The rate showed a typical case of substrate inhibition for high 1-decene concentration. The rate varied with a linear dependence on P-CO up to a CO partial pressure of 5-6 MPa in contrast to the general trends; for most of the rhodium-phosphine catalyzed hydroformylation reactions, severe inhibition of rate is observed with an increase in CO pressure. A rate equation has been proposed, which was found to be in good agreement with the observed rate data within the limit of experimental errors. The kinetic parameters and activation energy values have been reported.
Keywords: 1-decene; Hydroformylation; kinetics; ossification; supported ossified

Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite

Synthesis, characterization and catalytic study of mesoporous carbon materials prepared via mesoporous silica using non-surfactant templating agents - Pagar, Nitin S.; Karandikar, Prashant R.; Chandwadkar, Asha J.; Deshpande, Raj M. (Journal of Porous Materials, 2020)
Mesostructured silica materials with surface area in the range of similar to 700-900 m(2)/g have been prepared using hydroxy-carboxylic acid compounds such as tartaric acid, malic acid and citric acid (low cost non-surfactant template/pore forming agents) and tetraethylorthosilicate (TEOS) as silica source by sol-gel reaction. The templates were removed by either soxhlet extraction or calcination method. Mesoporous carbon molecular sieves were then prepared by carbonizing sucrose inside the pores of the above prepared mesoporous silica using sulfuric acid as a catalyst. The materials were characterized by FTIR spectroscopy, powder X-ray diffraction (XRD), N-2-sorption studies, microanalysis, thermal analysis and transmission electron microscopy (TEM). The resulting carbon material shows relatively higher surface area (similar to 1100 m(2)/g), narrow pore size distribution and pore diameter of 4-5 nm. The mesoporosity of carbon material arises from interconnecting channels arrangements of mesoporous silica template. The mesoporous carbon material was used as a support for the immobilization of rhodium complex [HRhCO(TPPTS)(3)] by ossification method. The prepared catalyst has been tested for the hydroformylation of higher olefins. The activity of the catalyst was improved by 20-30% as compared to the catalyst prepared from a conventional activated carbon support.
Keywords: Carbonization; Hydroformylation; Immobilization; Low cost templates; mesoporous carbon; Mesoporous silica

Kinetics of 1-decene hydroformylation in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of a cosolvent - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2021)
The kinetics of hydroformylation of 1-decene has been studied in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of N-methyl pyrrolidone as a cosolvent at 383-403 K. The rate was found to be first order, with concentrations of catalyst and olefin and partial order, with concentrations of hydrogen in the liquid phase. The plot of rate versus excess ligand and CO concentrations passed through maxima, indicating negative order dependence at higher concentrations. These trends have been interpreted based on the established hydroformylation mechanism. High selectivity towards the linear aldehyde was maintained (n: iso ratio > 30). An empirical rate equation has been proposed which was found to be in good agreement with the observed rate data within the experimental error. The activation energy was evaluated to be 74.76 kJ/mol.
Keywords: 1‐ aqueous‐ biphasic; cosolvent; decene; Hydroformylation; kinetics; rh‐ sulfoxantphos

Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands

Hydroformylation of olefins by metals other than rhodium - Kumar, Rohit; Chikkali, Samir H. (Journal of Organometallic Chemistry, 2022)
Metal catalyzed hydroformylation of alkenes is an atom economic transformation to construct useful aldehydes and is being industrially practiced for decades. The most commonly used metal for this transformation on an industrial scale is rhodium. However, rhodium is rare, costly, and is depleting at a skyrocketing rate. Therefore, finding a suitable alternative to rhodium for metal-catalyzed hydroformylation has been on the radar of many academic and industrial researchers. This review presents the scientific advancements reported in the hydroformylation reaction using metals other than rhodium. An overview of recent progress in palladium, iridium, ruthenium, cobalt, platinum, and iron-catalyzed hydroformylation is presented. Hydroformylation of alkenes and alkynes, using syngas as well as syngas surrogates is examined. The evaluation of the current status of non-rhodium metals in hydroformylation suggests that the field is still in a nascent stage and, except cobalt, no other metal poses a significant challenge to the dominance of rhodium. Deep mechanistic understanding of rate-limiting elementary steps in the non-rhodium metals is largely missing and thus only limited success is reported. Intense research on ligand design, mechanistic understanding, and choice of non-rhodium metal precursors may change this scenario in near future.
Keywords: aldehydes; alkenes; catalysis; Hydroformylation; Non-rhodium metals

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst

Iron-catalyzed magnesium-mediated formal hydroformylation of alkynes and alkenes - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (ChemCatChem, 2023)
Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is iron-catalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces alpha,beta-unsaturated aldehydes in good to excellent conversion. Mechanistic investigations revealed the presence of vinyl magnesium intermediate, the kinetic study disclosed the first-order dependence of the reaction on iron loading, and the control experiment authenticated the iron catalyst's homogeneous nature. The scope of this methodology was amplified, and 20 alkenes were examined. [Fe(acac)(3)] in the presence of ligand, alkyl magnesium halide, and dimethyl formamide catalyzed the hydroformylation of alkenes and displayed good to excellent conversion. An earth-abundant iron catalyst offering a syngas cylinder-free safe alternative to high-pressure hydroformylation has been reported.
Keywords: aldehydes; alkenes; Alkynes; Hydroformylation; iron catalysis

Rh-catalyzed asymmetric hydroformylation of olefins using phosphorus ligands - Kumar, Rohit; Sen, Anirban; Chikkali, Samir H. (Journal of chemical sciences, 2023)
Easily accessible BINOL-based monodentate phosphite ligand L1 and hybrid ligand L2 have been synthesized in good yield by following a one-pot, two-step protocol. A single 31P resonance at 146.6 ppm confirmed the formation of L1. Subsequent 1-2D NMR and mass spectrometric analysis authenticated the existence of L1. These ligands afforded excellent activity and regio-selectivity in the Rh-catalyzed AHF of styrenic substrates. L1 showed excellent regioselectivity but did not discriminate between the two enantiomers, while L2 displayed an enantiomeric excess (ee) of up to 20%. In our attempts to understand the reasons for low ee, the coordination behavior of L2 was investigated. The coordination study revealed that L2 coordinates with the Rh as a monodentate ligand, although there are two P-sites. It was found that only the phosphine arm was coordinated to the Rh and the phosphite arm stayed away from the Rh core at the ambient temperature, leading to moderate ee.Graphical abstractOne-step synthesis of a phosphite (L1) and a phosphine-phosphite (L2) ligand and their implication in the asymmetric hydroformylation of olefins with excellent regioselectivity (>95%) and moderate enantioselectivity (up to 20%) is reported.
Keywords: catalysis; coordination; Hydroformylation; Phosphine-phosphite ligand; Phosphite ligand